Bacteria-induced aggregation of bioorthogonal gold nanoparticles for SERS imaging and enhanced photothermal ablation of Gram-positive bacteria. Issue 30 (1st July 2019) - Wang, Huijie; Ouyang, Wenwen; Zhang, Xuerui; Xue, Jing; Lou, Xiaoran; Fan, Ranran; Zhao, Xiaonai; Shan, Lianqi; Jiang, Tingting
Abstract : A theranostic strategy based on biorthogonal cycloaddition was designed to form GNP aggregates, enabling bacterial SERS imaging and photothermal therapy. Abstract : The challenge in antimicrobial photothermal therapy (PTT) is to develop strategies for decreasing the damage to cells and increasing the antibacterial efficiency. Herein, we report a novel theranostic strategy based on bacteria-induced gold nanoparticle (GNP) aggregation, in which GNPs in situ aggregated on the bacterial surface via specific targeting of vancomycin and bioorthogonal cycloaddition. Plasmonic coupling between adjacent GNPs exhibited a strong "hot spot" effect, enabling effective surface enhanced Raman scattering (SERS) imaging of bacterial pathogens. More importantly, in situ aggregation of GNPs showed strong NIR adsorption and high photothermal conversion, allowing enhanced photokilling activity against Gram-positive bacteria. In the absence of bacterial strains, GNPs were dispersed and showed a very low photothermal effect, minimizing the side effects towards surrounding healthy tissues. Given the above advantages, the bioorthogonal theranostic strategy developed in this study may find potential applications in treating bacterial infection and even multidrug-resistant bacteria.